COVID-19 in the elderly people and advances in vaccination approaches - Kuldeep Dhama; Shailesh Kumar Patel; Senthilkumar Natesan; Kranti Suresh Vora; Mohd Iqbal Yatoo; Ruchi Tiwari; Shailendra K Saxena; Karam Pal Singh; Rajendra Singh; Yashpal Singh Malik (Taylor & Francis Group, 2020)
The rapid worldwide spread of the COVID-19 pandemic, caused by the newly emerged severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has resulted in tens of millions of infections and over one million deaths. SARS-CoV-2 infection affects all age groups; however, those over 60 years old are affected more severely. Moreover, pre-existing co-morbidities result in higher COVID-19-associated mortality in the geriatric population. This article highlights the associated risk factors of SARS-CoV-2 infection in older people and progress in developing COVID-19 vaccines, especially for efficient vaccination of the older population. There is also a summary of immunomodulatory and immunotherapeutic approaches to ameliorate the outcome of COVID-19 in older individuals.